Neoantigen Quantity and Quality in Relation to Pancreatic Cancer Survival - Levink, Iris J. M.; Brosens, Lodewijk A. A.; Rensen, Sander S.; Aberle, Merel R.; Olde Damink, Steven S. W.; Cahen, Djuna L.; Buschow, Sonja I.; Fuhler, Gwenny M.; Peppelenbosch, Maikel P.; Bruno, Marco J. (Frontiers in Medicine, 2022)
Introduction: Factors underlying antitumor immunity in pancreatic cancer (PC) are poorly understood. We hypothesized that not neoantigen quantity, but quality is related to immune cell infiltration and survival. Methodology: We performed genomic and transcriptomic profiling of paired normal, tumor tissue of 13 PDAC patients with distinct survival times. Additionally, neoantigens prediction and immunological profiling was performed. Results: The proportion of neoantigens with a low similarity-to-self score was higher in short-term survivors (P<0.0001), while mutational load, and burden, similarity-to-known-pathogens and immunogenicity of neoantigens were not associated with immune cell infiltration or survival. Discussion: Not tumor mutational load or neoantigen quantity, but a low similarity-to-self score was associated to immune cell infiltration and survival.